2014
DOI: 10.1007/s00253-014-5640-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a multi-function processive endoglucanase CHU_2103 from Cytophaga hutchinsonii

Abstract: Cytophaga hutchinsonii is a Gram-negative gliding bacterium which can efficiently degrade crystalline cellulose by an unknown strategy. Genomic analysis suggests the C. hutchinsonii genome lacks homologs to an obvious exoglucanase that previously seemed essential for cellulose degradation. One of the putative endoglucanases, CHU_2103, was successfully expressed in Escherichia coli JM109 and identified as a processive endoglucanase with transglycosylation activity. It could hydrolyze carboxymethyl cellulose (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 32 publications
2
45
1
Order By: Relevance
“…The crystal structure of Cel5B supports this suggestion, since the predicted open active site is consistent with a nonprocessive mode of action. Our results indicating the lack of processivity of Cel5B and Cel9C contradict earlier reports (23,38). The earlier studies lacked controls of known processive and nonprocessive enzymes and used amorphous cellulose (RAC) as the substrate in the processivity assays.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The crystal structure of Cel5B supports this suggestion, since the predicted open active site is consistent with a nonprocessive mode of action. Our results indicating the lack of processivity of Cel5B and Cel9C contradict earlier reports (23,38). The earlier studies lacked controls of known processive and nonprocessive enzymes and used amorphous cellulose (RAC) as the substrate in the processivity assays.…”
Section: Discussioncontrasting
confidence: 57%
“…Three of the nine predicted endoglucanase-encoding genes, cel5A (CHU_1107), cel5B (CHU_2103), and cel9B (CHU_1335), have been disrupted by insertion mutagenesis, but these single-gene mutations did not result in obvious defects in cellulose utilization (22,23).…”
mentioning
confidence: 99%
“…Mn 2+ and K + had no obvious effect on the enzyme. These results mostly agree with previous reports with the exception of glucanase activity inhibited by Mn 2+ in the studies (Liu et al, 2010;Takehara et al, 1981;Yan, 2008;Zhang et al, 2014). The difference may be due to the structure of gkdA, which has a multifunctional binding region different from the previously mentioned glucanase.…”
Section: Characterization Of Recombinant Enzymesupporting
confidence: 82%
“…Zhu et al reported that an outer membrane endoglucanase, ChCel5A, from C. hutchinsonii could hydrolyze microcrystalline cellulose to cellobiose and cellotriose (15). Another cell surface endoglucanase, CHU_2103, was shown to be a processive endoglucanase (26). However, whether cell surface degradation was the main mechanism of cellulose utilization by C. hutchinsonii was still unknown.…”
Section: Discussionmentioning
confidence: 99%